Collaborative multiple micro air vehicles' localization and target tracking in GPS-denied environment from range–velocity measurements. Issue 2 (June 2018) - Sarras, Ioannis; Marzat, Julien; Bertrand, Sylvain; Piet-Lahanier, Hélène
We treat the problem of simultaneous collaborative multiple micro air vehicles' localization and target tracking using time-varying range and (relative and absolute) velocity measurements. The proposed solution combines robustly local nonlinear observers that estimate the relative positions between agents and their neighbors, and cooperative filters that fuse each agent's local estimates to globally localize them with respect to the target (and therefore to each other). These estimates are then introduced in a dynamic consensus-type control law that ensures the global collective target tracking while simultaneously estimating the target's velocity, without needing any external reference which makes it applicable in GPS-denied environments. Finally, a simulation scenario is studied in order to show the efficiency of the proposed solution.